ANALISIS EFEKTIVITAS SISTEM PENGENDALIAN INTERNAL ATAS PERSEDIAAN BAHAN BAKU PADA CV ARSY MULIA TAMA - Lilik Ambarwati; Ika Rahmawati (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
One of the problems that is often faced by companies, especially large processing companies is regarding the processing of good raw material supplies. Because inventory is a fairly large company asset, so if the handling is not done properly, it will cause considerable losses to the company. This study aims to determine the effectiveness of the system of internal control of raw material inventory in the adoption of COSO at CV Arsy Mulia Tama. The object in the study was CV Asry Mulia Tama which is a sugar producer company. The analytical method used is descriptive data analysis method. Data collection techniques, by observing the company, conducting interviews, and conducting literature studies with books, literature, materials obtained during lectures that are relevant to the problems studied. The results showed internal control of raw material supplies at CV Asry Mulia Tama has not been fully effective, in which the company management has implemented the concepts and principles of internal control, and there are several procedures that reflect the concept of internal control that adopts COSO. But in control activities that still need to be improved due to the existence of multiple functions in the reception and storage section.